Stories about building history told by wooden elements – case studies from Eastern Austria. Issue 2 (17th February 2018) - Grabner, Michael; Buchinger, Günther; Jeitler, Markus
ABSTRACT: The intention of this article is to show the benefit of an interdisciplinary approach within the various disciplines of building research (architectural archeology, art history, archive research, dendrochronology, etc.). The exact determination of the age of historical timber is undoubtedly the most important contribution of dendrochronology to building research. The significance of dendrochronological dates is discussed in detail—problems of reuse, repair, drying time, and differences between felling and building dates are demonstrated. Several case studies in Eastern Austria showed a difference of two to four years between felling and building. To answer questions of where the timber came from, dendroprovenancing was introduced to Eastern Austria. First results showed that it will be possible to differentiate the origin of timber between Eastern Austria and regions where rafts started towards Vienna, via the river Danube. The results showed that it is important to combine building archaeology and archival analyses with the dendrochronological results.